The Role of Indonesia in Leading Efforts to Mitigate Climate Change in ASEAN in 2023 - Hartanto, Hartanto (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2024)
This research investigates Indonesia's pivotal role in spearheading initiatives aimed at addressing climate change in the ASEAN region through 2023. Using qualitative research methods, including document analysis, and literature review, this research explores the various strategies, policies, and actions undertaken by Indonesia to combat climate change on a regional scale. The findings highlight Indonesia's proactive stance, leadership efforts, and collaborative engagement within ASEAN to mitigate the impacts of climate change. By analysing Indonesia's contributions and challenges in leading climate change mitigation efforts, this study provides valuable insights for policymakers, stakeholders, and researchers involved in environmental governance and climate action in the ASEAN community. Keywords: Indonesia, ASEAN, climate change, mitigation efforts, regional leadership